Supply Chain 4.0: concepts, maturity and research agenda. Issue 2 (14th September 2019) - Frederico, Guilherme F.; Garza-Reyes, Jose Arturo; Anosike, Anthony; Kumar, Vikas
Abstract : Purpose: Industry 4.0 is one of the most emergent research topics attracting significant interest by researchers as well as practitioners. Many articles have been published with regards Industry 4.0; however, there is no research that clearly conceptualizes Industry 4.0 in the context of supply chain. This paper aims to propose the term "Supply Chain 4.0" together with a novel conceptual framework that captures the essence of Industry 4.0 within the supply chain context. As Industry 4.0 is inherently a revolution, and as revolutions are evolutionary, this research also aims to capture the evolution of Supply Chain 4.0 from maturity levels perspective to facilitate the formulation and development of Supply Chain 4.0 strategy. Design/methodology/approach: Following a deductive research approach and a qualitative strategy, a systematic literature review (SLR) was adopted as the research method seeking to understand the relationships among supply chain, Industry 4.0 and maturity levels research. The three phases of the SLR process utilized are: planning, conducting and reporting. A concept-oriented technique was applied to the outputs of the SLR to obtain the key constructs that would facilitate the development of the conceptual Supply Chain 4.0 framework. Findings: The SLR showed that there is limited research linking Industry 4.0 to supply chain. Nevertheless, it was possible to extract a set of thematic categories from the analysis of the articles which are referred to as constructs as they form the core of the conceptual Supply Chain 4.0 framework. These constructs are managerial and capability supporters, technology levers, processes performance requirements and strategic outcomes. Each of these constructs consists of a number of elements which are referred to as "dimensions" in this research and a total of 21 dimensions were identified during the SLR. The SLR also demonstrated that maturity propositions for Industry 4.0 are still embrionary and entirely missing in the context of supply chain. Hence, this research develops and proposes a maturity levels framework that is underpinned by the core constructs of Supply Chain 4.0 and the corresponding dimensions. As these proposed frameworks are conceptual, this research also identifies and proposes several research directions to help fortify the Supply Chain 4.0 concept. Research limitations/implications: This research argues that the frameworks are robust because the constructs and dimensions are grounded in the literature, thus demonstrating both theoretical and practical relevance and value. As Supply Chain 4.0 research is still in infancy, there is a range of open research questions suggested based on the frameworks that could serve as guides for researchers to further develop the Supply Chain 4.0 concept. Also, practitioners can use this framework to develop better understanding of Supply Chain 4.0 and be able to evaluate the maturity of their organizations. As the proposed frameworks are conceptual, they require further empirical research to validate them and obtain new insights. Originality/value: The SLR demonstrated a clear gap in literature with regards to Industry 4.0 in the context of supply chain, and also in the context of Industry 4.0 maturity levels for supply chain. This research is unique as it formulates and introduces novel frameworks that close these gaps in literature. The value of this research lies in the fact that it makes significant contribution in terms of understanding of Supply Chain 4.0 with a clear set of constructs and dimensions that form Supply Chain 4.0, which provides the foundation for further work in this area.